2012
DOI: 10.1021/ol302889t
|View full text |Cite
|
Sign up to set email alerts
|

A Sequential Pd/Norbornene-Catalyzed Process Generateso-Biaryl Carbaldehydes or Ketones via a Redox Reaction or 6H-Dibenzopyrans by C–O Ring Closure

Abstract: o-Biaryl carbaldeydes and ketones are obtained through the one-pot reaction of o-aryl iodides with o-bromobenzyl alcohols under the catalytic action of Pd and norbornene, in the presence of a base. The same reaction can also give dibenzopyrans by Pd and norbornene catalysis with a different termination, leading to C-O ring closure. In both cases the process first leads to a five-membered palladacycle, which controls C-C coupling, then to a seven-membered oxapalladacycle, which gives aldehydes and ketones or di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(37 citation statements)
references
References 55 publications
2
35
0
Order By: Relevance
“…Catellani and co-workers reported that the reaction of iodobenzenes with o -bromobenzylic alcohols bearing no benzylic hydrogen proceeded in the presence of a palladium catalyst and NBE to produce dibenzopyrans. 12 According to their procedure, 2a and 3a were treated with 5 mol% Pd(OAc) 2 , 1 equiv. of NBE, and 2.5 equiv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catellani and co-workers reported that the reaction of iodobenzenes with o -bromobenzylic alcohols bearing no benzylic hydrogen proceeded in the presence of a palladium catalyst and NBE to produce dibenzopyrans. 12 According to their procedure, 2a and 3a were treated with 5 mol% Pd(OAc) 2 , 1 equiv. of NBE, and 2.5 equiv.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that tertiary benzyl alcohols are essential for high-yield formation of the chromeno-2-quinolones because primary and secondary benzyl alcohols undergo oxidation under the reaction conditions, as reported by Catellani and coworkers. 12 …”
Section: Resultsmentioning
confidence: 99%
“…Thus, we decided to follow a different approach for the construction of biphenyl units based on a Pd/norbornene dual catalysis process [11]. As starting materials for this procedure, we prepared bromo derivative 2 , obtained from commercially available 6‐bromo‐veratraldehyde by addition of MeMgBr, oxidation to the corresponding methyl ketone and a further addition of MeMgBr, and iodo derivatives 3 and 4 as the result of the iodination with I 2 /HIO 3 of 2,3‐dimethyl‐ and 2,3,5‐trimethyl anisole, respectively (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…We tried then to apply the mentioned procedure,[11] reacting derivative 2 with 3 , or 4 , in the presence of catalytic amounts of Pd(OAc) 2 , 1.0 equiv of norbornene and dry K 2 CO 3 in dry DMF at 105°C. Under this condition, after 24 hours, we were able indeed to isolate derivative 5 ( R =H) in 64% yield.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, this palladium/norbornene-catalyzed C-H activation and functionalization reaction has been proven to be a powerful tool for the construction of complex molecules in a one-pot fashion [7,8]. In this context, we have successfully applied this methodology to the synthesis of many compounds, including natural product derivatives [9][10][11][12][13][14][15][16][17][18][19][20]. Notably, in 2011, we enriched the versatility of the Catellani reaction by the synthesis of dibenzo[b,f ]azepines [21].…”
Section: Introductionmentioning
confidence: 99%